IELTS to success : preparation tips and practice tests - Van Bemmel, Eric.; Tucker, Janina; Nguyễn Thành Yến (Tp.HCM : Tp.HCM, 2000)
Introduction to the IELTS test; Skills and strategies for IELTS.
International English language testing system.
Keywords: English language; IELTS; International English language testing system; English language -- Study and teaching -- Textbooks for foreign speakers; English language -- Examinations; English language -- Australia -- Study and teaching -- International English language testing system